Aggregating Claims Data Across Payers: Approaches, Challenges, and Lessons Learned From the Comprehensive Primary Care Initiative. (January 2020) - Mutti, Anne; Taylor, Erin Fries; Peikes, Deborah; Jin, Janel; Liao, Kristie; Tu, Ha
The Comprehensive Primary Care (CPC) initiative fueled the emergence of new organizational alliances and financial commitments among payers and primary care practices to use data for performance improvement. In most regions of the country, practices received separate confidential feedback reports of claims-based measures from multiple payers, which varied in content and provided an incomplete picture of a practice's patient panel. Over CPC's last few years, participating payers in several regions resisted the tendency to guard data as a proprietary asset, instead working collaboratively to produce aggregated performance feedback for practices. Aggregating claims data across payers is a potential game changer in improving practice performance because doing so potentially makes the data more accessible, comprehensive, and useful. Understanding lessons learned and key challenges can help other initiatives that are aggregating claims or clinical data across payers for primary care practices or other types of providers.